Precipitation, Synthesis, and Characterization of Hydroxyapatite Derived from Gonggong Snail Shells (Strombus canurium) - Maritza, Najla; Dewanti, Beauty Suestining Diyah; Yuliatun, Leny (Universitas Gadjah Mada, 2026)
The gonggong snail shell contains high calcium, reaching 67.70%, which potential to be used as a source of natural hydroxyapatite. Hydroxyapatite can be used as a biomaterial for bone substitutes because it is able to integrate with bone tissue without causing toxic effects or inflammation. The purpose of this study was to analyze the effect of temperature and precipitation synthesis time on the characteristics of hydroxyapatite produced from the gonggong snail shell for bone substitute biomaterials. The results showed that precipitation at 900 °C for 4 h is the best solution for synthesizing hydroxyapatite with a Ca/P ratio of 2.76, closely approximating the stoichiometric value of HAp. SEM revealed that the synthesized HAp exhibited a spherical morphology with a tendency to form granular aggregates. FTIR confirmed the presence of characteristic PO43− and OH− functional groups. XRD analysis indicated that primary phase of the synthesized material was HAp, consistent with JCPDS data. The optimal immersion time and temperature for fabricating at 900 °C for 4 h in HAp:alginate ratio (w/w) of 2.5:7.5 (HAPT2C) based on their mechanical properties. But HAp:alginate ratio (w/w) of 5:5 (HAPT2A) demonstrated higher water absorption compared to HAPT2C in the water uptake test. HAp from gonggong snail shell are promising biomaterial candidates for bone substitution applications, warranting further investigation through in vitro and in vivo biocompatibility studies.